1999
DOI: 10.1126/science.284.5415.765
|View full text |Cite
|
Sign up to set email alerts
|

A Cell's Sense of Direction

Abstract: In eukaryotic cells directional sensing is mediated by heterotrimeric guanine nucleotide-binding protein (G protein)-linked signaling pathways. In Dictyostelium discoideum amoebae and mammalian leukocytes, the receptors and G-protein subunits are uniformly distributed around the cell perimeter. Chemoattractants induce the transient appearance of binding sites for several pleckstrin homology domain-containing proteins on the inner face of the membrane. In gradients of attractant these sites are persistently pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
792
2
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 836 publications
(821 citation statements)
references
References 57 publications
24
792
2
3
Order By: Relevance
“…While previous studies demonstrated neurite outgrowth towards a neurotrophic factor source, the concentration pro®le was ill-de®ned. For example, neurite outgrowth towards a point source was studied, with the source created either by micropipetting factors at a speci®c location in culture media 18,19,38 or using explants which released the factors of interest. 28 In both examples, the concentration pro®le was either poorly de®ned 29 or Gaussian, 22 and depended upon the experimental geometry and other parameters used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies demonstrated neurite outgrowth towards a neurotrophic factor source, the concentration pro®le was ill-de®ned. For example, neurite outgrowth towards a point source was studied, with the source created either by micropipetting factors at a speci®c location in culture media 18,19,38 or using explants which released the factors of interest. 28 In both examples, the concentration pro®le was either poorly de®ned 29 or Gaussian, 22 and depended upon the experimental geometry and other parameters used.…”
Section: Discussionmentioning
confidence: 99%
“…7,39 At the nerve ®ber terminus, the growth cone is believed to guide the axon by sampling the environment for either positive or negative signals using ®lopodial and lamellar protrusions. 16,34,49 This sampling, comparing and decision-making procedure is believed to be a concentration gradient-dependent action, 38,49 which evokes a set of intracellular events involving cytoplasmatic second messengers. 43 A gradient of the cytoplasmatic second messenger may signal the preferential incorporation of new plasma membrane material and asymmetric cytoskeleton reorganization at the growth cone that is required for the appropriate orientation of neurites.…”
mentioning
confidence: 99%
“…According to Parent and Devreotes (1999), theories to explain chemotaxis (e.g. in Dictyostelium discoideum) should account for high sensitivity (to gradients as low as 2%), accuracy, directional sensing independent of motion, and also independent of the actin cytoskeleton.…”
Section: Responses To External Signalsmentioning
confidence: 99%
“…In the absence of an external gradient, processes form in random directions (Parent and Devreotes, 1999). Chemotaxis in Dictyostelium modifies motility behaviors that control the location of the pseudopod, and consequently whether the cell will turn (Williams and Harwood, 2003).…”
Section: Comparing Migration Of Lateral Mesoderm To Chemotaxismentioning
confidence: 99%